2016
DOI: 10.3892/or.2016.4709
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits hypoxia-induced epithelial-mesenchymal transition in pancreatic cancer cells via suppression of the hedgehog signaling pathway

Abstract: Abstract. Hypoxic microenvironment, a common feature of pancreatic cancer, is associated with tumor proliferation, metastasis and epithelial-mesenchymal transition (EMT) changes. In recent years, many natural agents, including curcumin, have been proven to possess the ability to inhibit the progression of pancreatic cancer. However, whether curcumin is able to suppress hypoxia-induced pancreatic cancer progression and the underlying mechanisms are still not fully elucidated. The aim of the present study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…Curcumin is a bioactive natural compound, which has been proven to restrain initiation, progression and metastasis of multifarious tumors, including pancreatic cancer (8). More importantly, curcumin is associated with minimal toxicity and it is safe at a high dose, as demonstrated by human clinical trials, in contrast with conventional cytotoxic drugs (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Curcumin is a bioactive natural compound, which has been proven to restrain initiation, progression and metastasis of multifarious tumors, including pancreatic cancer (8). More importantly, curcumin is associated with minimal toxicity and it is safe at a high dose, as demonstrated by human clinical trials, in contrast with conventional cytotoxic drugs (35).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin exerts its anticancer effects by targeting multiple intracellular signaling pathways, including mitogen-activated protein kinase (MAPK), nuclear factor (NF)-ÎșB, Akt and Wnt/ÎČ-catenin, among others (5)(6)(7). In addition, we recently demonstrated that curcumin inhibited hypoxia-induced epithelial-to-mesenchymal transition (EMT) in pancreatic cancer cells via blockade of the hedgehog signaling pathway (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Especially for high-grade gliomas, the activation or inhibtion of the Hedgehog signaling pathway has a remarkable impact on cell proliferation. 39 There are also numbers of research revealed that Curcumin has specific regulation to Hedgehog signaling pathway and EMT process 7,40,41 in several cancer cells including pancreas, colon, leukemia, prostate carcinoma and glioblastomas. 8,[42][43][44] Islam SS et al and Xu X et al 9,10 point out that the Hedgehog signaling pathway activates EMT process to promote tumorigenicity and stemness.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] In our previous researches, we illustrated that Curcumin, the ingredient of turmeric, suppressed the activity of Hedgehog signaling pathway by mediating the protein expression including Gli1, SMO and Sufu. 7,8 And Curcumin could also prevent the EMT in different tumor cells. 9,10 With the interruption of EMT, Curcumin might cover the shortage of g-irradiation (induction of EMT).…”
Section: Introductionmentioning
confidence: 99%